PENGARUH TRATEGI PEMBELAJARAN MELALUI TONTONAN FILM ANIMASI DORA THE EXPLORER TERHADAP PENGUASAAN KOSAKATA BAHASA INGGRIS ANAK USIA 5-6 TAHUN - Afriani, Riska; A. Azizah Amal; Sri Rika Amriani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to determine the effect of a learning strategy through watching the animated film Dora the Explorer on the English vocabulary mastery of children aged 5–6 years at RA IT Nurul Ilmi. This study employed a quantitative approach with a quasi-experimental design using a Non-Equivalent Control Group Design. The sample consisted of 20 children selected through purposive sampling, divided into an experimental group (10 children) and a control group (10 children). Data were collected through observation and documentation, then analyzed using descriptive statistics and the non-parametric Wilcoxon Signed Rank Test and Mann-Whitney U Test with SPSS version 26. The results showed that the mean vocabulary score of the experimental group increased from 16.30 (pre-test) to 24.90 (post-test), while the control group increased from 16.00 to 18.60. The Wilcoxon test in the experimental group produced a Z value of -2.823 with Asymp. Sig. (2-tailed) of 0.005 (p < 0.05), indicating a significant improvement after treatment. The Mann-Whitney U Test on post-test data showed Asymp. Sig. (2-tailed) of 0.004 (p < 0.05), indicating that the experimental group significantly outperformed the control group after treatment. It is concluded that the learning strategy through watching the animated film Dora the Explorer has a significant effect on improving English vocabulary mastery, particularly nouns, verbs, adjectives, and adverbs, among children aged 5–6 years.